A utilização de serviços web providos por SOA em geradores de aplicação desenvolvidos com linguagens de padrões - Rodrigues, Kamila Rios da Hora (2009)
System reuse is a Software Engineering technique that proposes the construction of software systems from existing artifacts. One way to develop systems reusing code and project in a specific domain is using application generators. These generators automate part of the development process, reduce costs, allow the increase of the development team productivity, enhance systems quality and minimize error insertion arising from the implementation phase. The GawCRe (Web based Application Generator to the Rehabilitation Clinic domain) was developed using the software product lines technique based in the SiGCli (Rehabilitation Clinics Management System) pattern language. This generator went through some maintenance in order to allow the MySQL RDBMS usage, as well as to carry out version control of the generated applications and increase its domain to others related to it. Currently, there is interest in the usage of Service Oriented Architectures (SOA) to support the construction of software applications that use services available in a network, as the Web. These services are an implementation of well-defined business functionality that can be used by clients of different applications. The reutilization of available services in the construction of new Web systems is increasing, reducing the rework and facilitating the maintenance of these systems. This master's thesis presents an approach to modify application generators in a way that its domain is increased by the use of Web Services provided by Service Oriented Architecture. This architecture eases systems' adaptation, making them dynamic, as their services can be swapped in runtime. This allows future maintenances to be eased, because modifications in the services are reflected in the applications without user intervention. The GAwCRe undergone for maintenance to support the use of Web Services provided by a SOA, thereby, broadening its domain. A case study was conducted using the GAwCRe and some Web Services attempt to evaluate the combined use of SOA and Application Generators.